MENGUPAYAKAN KOMUNIKASI ANTAR STAKEHOLDER DALAM PEMBANGUNAN KEHUTANAN - Sapja Anantanyu (Universitas Sebelas Maret, 2003)
Natural disaster, landslide and floods, progressively often happened in various indonesian regions when the rains season. Denudation of forest, effect of deforestation process, affect at energy support of nature derivation and declining the quality of ecology, have generated disaster to human life. Ruining of forest have become common phenomenon us chronic social pathology form in Indonesian societes. It is needed an effort to alter situation in this lime (recent status), that is ruining of forest on a large scale, becoming situation which is normative/expected/desirab/e status, that is everlastingly forest development. Development communications play as bridging the gap lo link between various side which have competence and have komitment to forest existence.